Complement component 1, q subcomponent binding protein (C1QBP) in lipid rafts mediates hepatic metastasis of pancreatic cancer by regulating IGF‐1/IGF‐1R signaling. Issue 7 (24th June 2017) - Shi, Haojun; Fang, Winston; Liu, Minda; Fu, Deliang
Abstract : Pancreatic cancer shows a remarkable predilection for hepatic metastasis. Complement component 1, q subcomponent binding protein (C1QBP) can mediate growth factor‐induced cancer cell chemotaxis and distant metastasis by activation of receptor tyrosine kinases. Coincidentally, insulin‐like growth factor‐1 (IGF‐1) derived from the liver and cancer cells itself has been recognized as a critical inducer of hepatic metastasis. However, the mechanism underlying IGF‐1‐dependent hepatic metastasis of pancreatic cancer, in which C1QBP may be involved, remains unknown. In the study, we demonstrated a significant association between C1QBP expression and hepatic metastasis in patients with pancreatic cancer. IGF‐1 induced the translocation of C1QBP from cytoplasm to lipid rafts and further drove the formation of CD44 variant 6 (CD44v6)/C1QBP complex in pancreatic cancer cells. C1QBP interacting with CD44v6 in lipid rafts promoted phosphorylation of IGF‐1R and thus activated downstream PI3K and MAPK signaling pathways which mediated metastatic potential of pancreatic cancer cells including proliferation, apoptosis, invasion, adhesion and energy metabolism. Furthermore, C1QBP knockdown suppressed hepatic metastasis of pancreatic cancer cells in nude mice. We therefore conclude that C1QBP in lipid rafts serves a key regulator of IGF‐1/IGF‐1R‐induced hepatic metastasis from pancreatic cancer. Our findings about C1QBP in lipid rafts provide a novel strategy to block IGF‐1/IGF‐1R signaling in pancreatic cancer and a reliable premise for more efficient combined modality therapies. Abstract : What's new? Hepatic metastasis constitutes the final stage of pancreatic cancer and is associated with extremely poor prognosis. To improve detection and treatment of hepatic metastasis, however, greater understanding of the regulatory mechanisms driving dissemination to the liver is needed. Here, the authors reveal an association between complement component 1, q subcomponent‐binding protein (C1QBP) expression and hepatic metastasis in pancreatic cancer patients. Specifically, C1QBP was found to interact with cell adhesion variant CD44v6 in lipid rafts and thereby regulate insulin‐like growth factor‐1 signaling pathways, enhancing metastatic potential. The findings highlight C1QBP as a promising therapeutic target for hepatic metastasis in pancreatic cancer.